MARKETING FOR INNOVATION STARTUP PRE-SEED STAGE - B. Tokarev (Вестник университета)
The article is devoted to a problem of understanding the marketing place and essence for innovation product startup. It is shown that innovation startup marketing consists of a complex actions differ at any stages. Startup marketing model to find the idea of an innavative technological product is formed. The review ant the list of marketing actions for pre-seed stage of innovation product life cycle are made. It is shown that consumers are differ from one stage life cycle to another. The composition of actions for understanding the market and consumers is described.